Representation of Muara Takus Temple in the Stage Design of the 31st Srivijaya Festival 2023 - Didiek Prasetya; Mukhsin Patriansah; Husni Mubarat; Iqbal Maulana Yazid; M. Ridwan (Sanggitarupa, 2026)
The 31st Srivijaya Festival 2023 was a cultural arts event that highlighted historical values and regional cultural identity. The festival involved participants from 17 regencies and municipalities across South Sumatra. One of the key elements in the event was the stage design, which adapted the visual form of Muaro Takus Temple. The selection of Muaro Takus Temple was based on its historical significance related to the glory of the Srivijaya Kingdom and its distinctive architectural features, particularly its stupa form and red-brick construction. This study aims to examine and analyze the process of cultural transformation and representation from the temple’s architectural form into the stage design. The research employed a descriptive qualitative method with an interpretative approach. Data were collected through observation, interviews, and documentation as primary sources, while literature studies from internet sources, social media, scientific articles, and relevant books served as secondary data. The validity of the data was established through data triangulation, which included documentation of the architectural form of Muaro Takus Temple, verification of relevant literature, and interpretative analysis using Stuart Hall's representation theory. The data were analyzed through data reduction, data presentation, and conclusion drawing. The findings reveal that the representation of Muaro Takus Temple was manifested through the application of visual elements, including form, line, color, texture, and space, which were derived from the temple’s architectural characteristics such as its tiered structure, red-brick material, and stupa shape. These elements were transformed into the main stage property, functioning not only as a performance backdrop but also as a symbol of the grandeur of Srivijaya as a maritime kingdom and a center for the dissemination of Buddhism in the Indonesian archipelago. Therefore, the stage design of the 31st Srivijaya Festival 2023 serves as a visual, aesthetic, and communicative representation of the cultural and historical values embodied in Muaro Takus Temple